In situ polymerization of sulfonated polyaniline in layered double hydroxide host matrix for corrosion protection. (19th February 2018) - Du, Peng; Qiu, Shihui; Liu, Chengbao; Liu, Guangzhou; Zhao, Haichao; Wang, Liping
Abstract : Sulfonated polyaniline/layered double hydroxides were synthesized via in situ polymerization in host matrix, displaying significant anti-corrosive performance. Abstract : The hybrid material of sulfonated polyaniline/Mg Al layered double hydroxides (SPANi/LDHs) was obtained through polymerization of o -aminobenzenesulfonic acid and aniline in the galleries of LDHs. The structure of SPANi/LDH was characterized by field-emission scanning electron microscopy, X-ray diffraction, Fourier transformed infrared and Raman spectroscopy. The as-prepared SPANi/LDH showed an irregular lamellar shape with an average diameter of 4–6 μm and offset of XRD reflections, which revealed that SPANi successfully grew between the LDH interlayers and expanded the interlayered structure slightly. Besides, the monolayer thickness of the SPANi/LDH was about 2.67 nm, which exhibited a significant structure of a nanosheet. The as-prepared SPANi/LDHs hybrids were applied to waterborne epoxy coatings for steel substrates and exhibited significant corrosion protection capacities compared with those of neat epoxy and pure SPANi blended epoxy composites. The electrochemical impedance spectroscopy (EIS) technique was used to describe the electrochemistry dynamics and remarkable corrosion protection performance. Furthermore, corrosion products beneath the epoxy coatings immersed in a 3.5 wt% NaCl aqueous solution were also investigated, which indicated the barrier property and passivation effect of SPANi/LDH. In addition, the mechanism of corrosion inhibition was explored via the analysis of rust layers, and the barrier effect and passivation effect of the composite materials was also demonstrated.